2014
DOI: 10.1186/s13570-014-0017-2
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of pastoral corridors: practices and politics in eastern Senegal

Abstract: The delineation and protection of transhumance corridors are increasingly seen as critical to maintaining livestock mobility in agropastoral areas of West Africa by allowing passage through areas of increasing cropping pressure. Understanding the local politics surrounding the mapping and protection of transhumance corridors is important for policy formulation. This study reports the findings of group meetings in nine local districts (communautés rurales) in eastern Senegal about recently mapped corridors. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Institutional realities within the region suggest that these systems will require cooperation and coordination among civil society organizations (customary pastoral authorities and pastoral associations) to govern pastoral resources in a flexible manner with more formal governance institutions at the local district level (e.g., commune) to protect these resources from competing land uses. As previous research has shown, these efforts are not easy and will require sustained efforts of negotiation and compromise at multiple levels of governance (Brottem 2014;Kitchell et al 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Institutional realities within the region suggest that these systems will require cooperation and coordination among civil society organizations (customary pastoral authorities and pastoral associations) to govern pastoral resources in a flexible manner with more formal governance institutions at the local district level (e.g., commune) to protect these resources from competing land uses. As previous research has shown, these efforts are not easy and will require sustained efforts of negotiation and compromise at multiple levels of governance (Brottem 2014;Kitchell et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Reciprocity often shapes access to these resources over time, but the imposition of rigid common property boundaries around resources and user groups is seen as unduly inhibiting livestock movements (Moritz et al 2013b). Thus the delineation and codification of corridors and encampment sites, seen by some as critical protections of key pastoral resources from competing land uses (Kitchell et al 2014), are seen by others as introducing rigidity into pastoral systems (Moritz et al 2013a). As described above, this tension reflects what Fernandez-Gimenez (2002) calls the Bparadox of pastoral land tenure^.…”
Section: Pastoral Tenure Institutions and Livestock Mobilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Research on pastoralism has given increasing recognition and support to traditional pastoralism, livestock spatial mobility (Kitchell et al 2014;Scoones 1995) and to rights of pastoral people to control and manage their grazing territories (Adriansen and Nielsen 2002;Swift 1991). It is argued that flexible livestock mobility reduces pastoralists' vulnerability to climate change and the likelihood of livestock-induced rangeland degradation (Brottem et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is argued that flexible livestock mobility reduces pastoralists' vulnerability to climate change and the likelihood of livestock-induced rangeland degradation (Brottem et al 2014). However, in most sub-Saharan African countries, such recognition has not yet translated into the protection and maintenance of traditional pastoralism of flexible mobility-based systems (Basupi et al 2017;Kitchell et al 2014).…”
Section: Introductionmentioning
confidence: 99%